Performance Comparison of Zirconia, Bismuth and Silica-doped Erbium Fiber for Optical Amplification - Mohamad, Sufian; Munira Markom, Arni; Sidik, Norbaiti; Chandra Paul, Mukul; Wadi Harun, Sulaiman (International Journal of Engineering and Technology, 2018)
Zirconia-based Erbium-doped fiber amplifier (Zr-EDFA) is improved material optical fiber with more than 4000 ppm erbium-doped concentration to solve global demand for huge capacity carrying data information, high speed transmission and long haul with specific devices of compactness. Thus, the length of Zr-EDFA is only 50 cm as gain medium. At input pump power -30 dBm, the highest optical gain is 34 dB (1530 nm wavelength) whereas 21 dB (1535 nm wavelength) at -10 dBm. Besides, the flatness gain 21 dB with fluctuation of 1 dB is recorded for Zr-EDFA. For performance comparison, Bismuth-based Erbium-doped fiber amplifier (Bi-EDFA) and Silica-based Erbium-doped fiber amplifier (Si-EDFA) were also investigated.Â Â